Kebersyukuran dan stres akademik pada mahasiswa bekerja (SUKMA : Jurnal Penelitian Psikologi, 2023)
Academic stress has a relationship with demands and pressures that affect academic performance. The purpose of this study is to examine the relationship between gratitude and academic stress in working college students. Participants in this study were working college students in Surabaya. There were 80 working college students at the ages of 18-27 who actively work either part time or full time jobs while pursuing college education. In the data collection, the researcher utilized an online questionnaire based on gratitude scale and academic stress scale. Sampling technique used in this study was purposive sampling. An analysis technique of rank spearman correlation coefficient was conducted to examine the relationship between gratitude and academic stress in working college students. implying a significant negative relation between gratitude and academic stress in working college students Therefore, promoting gratitude among working college students may be a strategy to deal with academic stress. Stres akademik memiliki hubungan dengan tuntutan dan tekanan sehingga mempengaruhi prestasi akademik. Tujuan dalam penelitian ini untuk mengkaji hubungan antara kebersyukuran dengan stres akademik pada mahasiswa bekerja. Partisipan dalam penelitian adalah 80 mahasiswa bekerja berusia 18-27 tahun yang aktif bekerja baik part time maupun full time sembari kuliah. Dalam pengumpulan data peneliti menggunakan kuesioner online, yang mengacu pada skala kebersyukuran dan skala stres akademik. Teknik sampling yang digunakan dalam penelitian ini yaitu purposive sampling. Teknik analisis korelasi rank spearman dilakukan untuk menguji hubungan antara kebersyukuran dengan stres akademik pada mahasiswa bekerja. hasil tersebut menunjukkan bahwa kebersyukuran memiliki hubungan negatif yang signifikan terhadap stres akademik pada mahasiswa bekerja. Oleh karenanya, kebersyukuran pada mahasiswa bekerja dapat menjadi solusi dalam menangani stres akademik.